Activation of ⁹³Nb nuclei on the linac LUE-40 of RDC “Accelerator” and determination of photonuclear reaction cross-sections - Vodin, O.M.; Deiev, O.S.; Olejnik, S.M. (Вопросы атомной науки и техники, 2019)
The bremsstrahlung spectra of medium-energy electrons (30…100 МeV) were calculated in GEANT4. Crosssections for photonuclear reactions were calculated in TALYS1.9. A convolution over the energy of the crosssections of one- and many-particle reactions with the bremsstrahlung flux density was performed. The numerical values of the yield of ⁹³Nb(γ,xn) ⁹³-xNb reactions, the activity of irradiated ⁹³Nb targets, and the average reaction cross-sections were obtained. The differences of the bremsstrahlung spectra from electrons with close initial energies were calculated. The shape of the difference spectra was analyzed. The contributions of the quanta of the lowenergy part of the difference spectrum and the quasi-monochromatic peak of the difference spectrum to the total activity of the targets were compared. An approach for correction of the experimental cross-sections of photonuclear reactions using the method of "bremsstrahlung spectra difference" was considered. Спектри гальмівного випромінювання електронів середніх енергій (30...100 МeВ) розраховувалися в GEANT4. Перерізи фотоядерних реакцій розраховувалися в TALYS1.9. Проведена згортка по енергії перерізів одно- і багаточастинкових реакцій з щільністю потоку гальмівного випромінювання. Отримано чисельні значення виходу реакцій ⁹³Nb(γ,xn) ⁹³-xNb, активності опромінених мішеней ⁹³Nb, середнє значення перерізів реакції. Розраховано різниці гальмівних спектрів від електронів з близькими початковими енергіями. Проведено аналіз форми спектрів різниці, виконано порівняння вкладів у повну активність мішеней, окремо квантів низькоенергетичної частини різницевого спектра і квазімонохроматичного піку різницевого спектра. Розглянуто підхід для коригування експериментальних перерізів фотоядерних реакцій при використанні методу «різниці гальмівних спектрів». Спектры тормозного излучения электронов средних энергий (30…100 МэВ) рассчитывались в GEANT4. Сечения фотоядерных реакций рассчитывались в TALYS1.9. Проведена свертка по энергии сечений одно- и многочастичных реакций с плотностью потока тормозного излучения. Получены численные значения выхода реакций ⁹³Nb(γ,xn) ⁹³-xNb, активности облученных мишеней ⁹³Nb, среднее значение сечений реакции. Рассчитаны разности тормозных спектров от электронов с близкими начальными энергиями. Проведен анализ формы спектров разности, выполнено сравнение вкладов в полную активность мишеней, отдельно квантов низкоэнергетической части разностного спектра и квазимонохроматического пика разностного спектра. Рассмотрен подход для корректировки экспериментальных сечений фотоядерных реакций при использовании метода «разности тормозных спектров».